Identification of a Gene Expression Signature Characterizing Clonal Fitness and Dominance in Vivo in a Murine Model of MLL-AF9 Leukemia - Mercier, Francois; Shi, Jiantao; Sykes, David; Kfoury, Youmna Sami; Yusuf, Rushdia Z.; Miller, Elizabeth; Vasic, Radovan; Zhu, Alex; Michor, Franziska; Hide, Winston; Scadden, David T. (Blood, 2014)
Rationale: Human malignancies are often composed of multiple, related clones that arise through a process of branching Darwinian evolution. In acute myeloid leukemia (AML), high-throughput DNA sequencing identifies clonal heterogeneity at the mutational level, but the downstream molecular pathways driving clonal fitness, and their impact on response to therapy are still poorly understood. We report on the development of a novel experimental tool that allows prospective tracking of clonal evolution at the functional level. Using a combination of murine models of AML and fluorescent protein labeling, we can measure clonal evolution in real time, serially isolate live clones competing in the same environment for phenotypic characterization, and correlate these findings with mutational, epigenetic and gene expression profiling. Methods: A clonal pre-leukemic cell line, derived from a murine granulocyte-macrophage progenitor infected with a retrovirus enforcing expression of the MLL-AF9 fusion protein, was labeled with a pool of lentiviruses driving the expression of multiple fluorescent proteins (FPs). From this cell line, fluorescently distinguishable sub-clones were selected and expanded. This pool of clones was transplanted in multiple recipients. Disease competition and evolution was tracked prospectively in primary recipients through repeated sampling of blood and bone marrow. Secondary leukemic cell lines were established from individual clones harvested at serial time points during growth in vivo. In order to study the cell-intrinsic characteristics acquired following exposure to the bone marrow microenvironment, these secondary cell lines were transplanted into additional recipients to measure engraftment potential, growth rate, cell cycle and apoptosis, gene expression profile and acquisition of secondary mutations. Results: By transplanting in competition multiple pre-leukemic clones in a cohort of primary recipients, we observed emergence of dominant clones during the development of AML. By sampling “winner” clones at different time points, we could observe the gradual acquisition of a cell-intrinsic growth advantage that was preserved in secondary transplantation, whereas control “loser” clones grew at a significantly lower rate. Functional characterization of the winner clones demonstrated a higher engraftment rate in vivo, whereas the self-renewal potential and growth rate in vitro was similar among winner and loser clones. By comparing the gene expression profile of leukemic stem cells isolated from various clones, we observed that the most aggressive clones share a common signature characterized by activation of multiple metabolic pathways, such as steroid biosynthesis and response to oxidative stress. Since these pathways are not activated in the less aggressive clones, we hypothesize that secondary genetic events that promote growth spontaneously occured in vivo. Functional validation of these pathways is underway and, in parallel, constitutes the basis of ongoing pooled genetic perturbation screens to identify novel therapeutic targets that impede malignant cell growth. No relevant conflicts of interest to declare.